EDUKASI KADER PKK MENJADI PERINTIS KAMPUNG DONOR DARAH MANDIRI SAAT PANDEMI COVID-19 - Aini, Resmi; Sulistyo, Andhy (Universitas Respati Yogyakarta, 2021)
The Corona Virus-19 (Covid-19) outbreak in Indonesia has caused many problems including blood supply which will be significantly affected by decreasing the amount of blood donated. The Blood Transfusion Unit (UTD) must be ready to move quickly in response to the changes that occur, where an adequate blood supply is most likely to be affected. Purpose: to encourage the community of Partners to become voluntary blood donors so that they can help residents in keeping the availability of blood safe during the Covid-19 Pandemic. Methods: cadres from members of Family Welfare Empowerment (PKK) Sungapan, Sriharjo, Imogiri, Bantul, were trained to carry out initial donor selection examinations including blood pressure checks, hemoglobin level checks, blood type checks and doing it independently so that it can increase the role of voluntary blood donors. This outreach activity is to educate the community to form a cadre of PKK mothers to be trained in conducting initial donor selection checks so that data can be used as a means of obtaining voluntary donors in Mitra areas and creating independent blood donor villages. Conclusion: PKK cadres have been able to provide counseling to residents and are able to check blood pressure, hemoglobin levels and blood type keywords: cadre, blood donation village